Qalbun Management in the Perspective of the Qur’an: Islam Psychologi Review on Mental Health - Ridwanda, Muhammad Liza (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Background and Objectives: Heart is not merely a biological organ, but the spiritual, emotional, and moral center of human life. The increasing prevalence of mental health problems in contemporary society highlights the need for a Qur’an-based conceptual model that can complement medical and psychotherapeutic approaches. This research aims to develop a conceptual framework of the Qalb Management Model, emphasizing spiritual (faith, piety), emotional (patience, sincerity, gratitude), and cognitive (reflection, contemplation) dimensions as alternative strategies for mental health care. Methods: The study employs a qualitative-descriptive library research method, analyzing Qur’anic verses containing the term qalb along with classical exegesis, prophetic traditions, and Islamic psychology literature. Main findings: Mental health, from a Qur’anic perspective, can be achieved through stages of purification of the heart (tazkiyat al-nafs), control of desires, attainment of inner tranquility, and ultimately psychological well-being. Practical applications include structured practices of remembrance (dhikr), Qur’anic recitation (tilawah), and worship-based interventions as non-pharmacological therapies. Contribution: The formulation of the Qalb Management Model as an integrative and applicable approach within Islamic psychology. Conclusion: qalb management can serve as a complementary model for modern mental health treatment. However, this study remains conceptual in nature and requires further empirical research to validate its effectiveness.